ÐŸÑ€Ð¸Ð¼ÐµÐ½ÐµÐ½Ð¸Ðµ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ð¾Ð¹ Ð¿Ð»Ð°Ñ†ÐµÐ½Ñ‚Ð°Ñ€Ð½Ð¾Ð¹ Ñ‚ÐºÐ°Ð½Ð¸ Ð¿Ñ€Ð¸ Ð¸Ð·Ð¾Ð¸Ð¼Ð¼ÑƒÐ½Ð¸Ð·Ð°Ñ†Ð¸Ð¸ Ð±ÐµÑ€ÐµÐ¼ÐµÐ½Ð½Ñ‹Ñ… Ð¶ÐµÐ½Ñ‰Ð¸Ð½ - Lutsenko, N. S.; Prokopyuk, O. S.; Bondarenko, I. A.; Geraskina, L. R.; Evtereva, I. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
There were monitored 59 women with manifested immunization. The pregnant women of one of the groups were subcutaneously introduced with cryopreserved placenta, the ones from the control group received non-specific desensibilizing therapy. Use of tissue therapy contributes to more stable proceeding of pregnancy, labor, improvement of the state of newborns, decreased frequency of complications in pregnant women, indices of perinatal morbidity.